PERLINDUNGAN KONSUMEN TERHADAP INFORMASI YANG TIDAK JELAS DALAM MENU MAKANAN DAN MINUMAN DI RESTORAN X DAN Y: Consumer Protections Against Unclean Information On The Food And Drink Menu At Restaurants X And Y - Muhammad Vachry Irsyad Prasanna; Anna Maria Tri Anggraini (Faculty of Law, Universitas Trisakti, 2025)
This study aims to examine the regulation and its implications of the obligation to include clear price information on food and beverage menus at Restaurants X and Y. The focus of the study is also directed at the problem is the role of the government in supervising business actors' compliance with the provisions of Law Number 8 of 1999 concerning Consumer Protection (UUPK) and Regulation of the Minister of Trade Number 35 of 2013. The method used is normative juridical with a qualitative descriptive approach, based on secondary data from laws and regulations, and the results of interviews with consumers and business actors. The research result and conclusion indicate that the inclusion of non-transparent price information on the menu at Restaurants X and Y has the potential to harm consumers and violate right to correct, clear, and honest information as stipulated in Article 4 of the UUPK and is contrary to provisions of Article 2 of Permendag 35/2013. In addition, weak supervision by the government has resulted in the absence of strict sanctions against business actors who violate. Therefore, more effective enforcement of regulations and education for business actors are needed to improve compliance and ensure protection of consumer rights.